2021
DOI: 10.21203/rs.3.rs-155982/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Nomogram based on Autophagy Related Genes for Predicting the Survival in Melanoma

Abstract: Background: Autophagy, a highly conserved lysosomal degradation pathway, isassociated with the prognosis of melanoma. However, prognostic prediction modelsbased on autophagy related genes (ARGs) have never been recognized in melanoma.In the present study, we aimed to establish a novel nomogram to predict the prognosisof melanoma based on ARGs signature and clinical parameters.Methods: Data from The Cancer Genome Atlas (TCGA) and the Genotype-TissueExpression (GTEx) databases were extracted to identify the diff… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 45 publications
(46 reference statements)
0
1
0
Order By: Relevance
“…Currently, several studies have reported immune-related molecular markers as prognostic markers for melanoma [29][30][31], but these prognostic markers had limitations. First, molecular markers in previous studies contained various genes, which increased the workload and cost in clinical practice and constrained the clinical utility of these molecular markers to some extent [29,32,33].…”
Section: Discussionmentioning
confidence: 99%
“…Currently, several studies have reported immune-related molecular markers as prognostic markers for melanoma [29][30][31], but these prognostic markers had limitations. First, molecular markers in previous studies contained various genes, which increased the workload and cost in clinical practice and constrained the clinical utility of these molecular markers to some extent [29,32,33].…”
Section: Discussionmentioning
confidence: 99%